Analisis Optimalisasi Ketersedian Stock Semen Gresik Di Gudang Distributor Wilayah Dki Jakarta - Sukarno, Novita Kartiningrum (Universitas Muhammadiyah Gresik, 2023)
Background – Distributor warehouses can experience excess or shortage conditions of cement stock and solutions that must be implemented when the distributor's warehouse experiences these conditions. Based on this reality, it is necessary to analyze the causes of excess and shortage of stock experienced by the warehouses of the distributors in question. Objective – This study aims to find out the cause of the warehouse being distributor experiencing excess and lack of stock and knowing the solutions applied by the company in meeting the stock levels standardized by Semen Gresik. Design / Methodology / Approach – The types of data used are primary data and secondary data. The research method used is qualitative research. Primary data is obtained through interviews with key informants, while secondary data is obtained from library studies, books, internet, and data obtained from internal companies. Findings – The results of this study indicate that the causes of stock over and lack of stock can be caused by given factors and information distortion factors. Research Implication – While the solution for following up the stock availability of Semen Gresik products in distributor warehouses for the causes caused by given factors is grouped based on warehouse stock conditions that are excess or lacking. While the solution to the causes caused by information distortion factors must be validated data in the system with stock data in the field to determine the next follow-up. In addition, the Area Manager must socialize to distributors and improve the system. Limitations – The researcher limited the relationship of problems related to the planning of sales targets, sales efforts, supply chains starting from upstream to distribution to packing plants, grinding plants, and distribution centers.